PENGARUH KEPERCAYAAN DAN LOVE OF MONEY TERHADAP KEPATUHAN PAJAK SUKARELA DAN PAKSAAN - Hariman Bone; Desi Indriani (Jurnal Akun Nabelo: Jurnal Akuntansi Netral, Akuntabel, Objektif, 2022)
The purpose of this research is determining the effect of trust and love of money on voluntary and enforced tax compliance of individual taxpayers in Samarinda. The population in this research are individual taxpayers in Samarinda. Based on data from KPP Pratama Samarinda, there were 15.461 individual taxpayers registered in 2019.  Sampling was conducted using a simple random method. The number of respondents in this study are 355. The primary data collection method used was a survey method. This study analyses the data using WarpPls 7.0 software. The result show that trust has a positive and significant effect on voluntary tax compliance. Meanwhile, the trust has no significant effect on enforced tax compliance. Love of money has a positive and significant effect on enforced tax compliance, but has no significant effect on voluntary tax compliance.